Legal Protection of Investors Investment Virtual Currency - Koeswanto, Ekka Sakti; Taufiq, Muhammad (JURNAL ILMIAH LIVING LAW, 2017)
The presence of Virtual Currency (Centcoin and Bitcoin) in Indonesia is well known by Indonesian people as a business by means of speculation with the aim of making a profit that is used by its users as a means of exchange, means of payment and business by way of investment. Then pay attention to the Law of the Republic of Indonesia Number 7 of 2011 concerning Currencies when Virtual Currency (Centcoin and Bitcoin) serve as a means of exchange or payment transactions in Indonesia by its users is contrary to the Act, however Law Number 7 Year 2014 on Trade, Law of the Republic of Indonesia Number 19 of 2016 on the amendment to Law of the Republic of Indonesia Number 11 of 2008 on Information and Electronic Transactions and Law of the Republic of Indonesia Number 8 of 1999 concerning consumer protection can provide legal protection for the public or investor users Virtual Currency (Centcoin and Bitcoin) in Indonesia.Keywords: Legal Protection, Virtual Currency (Centcoin and Bitcoin), the Electronic Commerce Transactions